Nitrification inhibitor chlorate and nitrogen substrates differentially affect comammox Nitrospira in a grassland soil - Shah, Anish S.; Hsu, Pei-Chun; Chisholm, Chris; Podolyan, Andriy; Cameron, Keith; Luo, Jiafa; Stenger, Roland; Carrick, Sam; Hu, Wei; Ferguson, Scott A.; Wei, Wenhua; Shen, Jupei; et al. (Frontiers in Microbiology, 2024)
Through the combined use of two nitrification inhibitors, Dicyandiamide (DCD) and chlorate with nitrogen amendment, this study aimed to investigate the contribution of comammox Nitrospira clade B, ammonia oxidizing bacteria (AOB) and archaea (AOA) to nitrification in a high fertility grassland soil, in a 90-day incubation study. The soil was treated with nitrogen (N) at three levels: 0 mg-N kg -1 soil, 50 mg-N kg -1 soil, and 700 mg-N kg -1 soil, with or without the two nitrification inhibitors. The abundance of comammox Nitrospira, AOA, AOB, and nitrite oxidising bacteria (NOB) was measured using qPCR. The comammox Nitrospira community structure was assessed using Illumina sequencing. The results showed that the application of chlorate inhibited the oxidation of both NH4 + and NO2 -in all three nitrogen treatments. The application of chlorate significantly reduced the abundance of comammox Nitrospira amoA and nxrB genes across the 90-day experimental period. Chlorate also had a significant effect on the beta diversity (Bray-Curtis dissimilarity) of the comammox Nitrospira clade B community. Whilst AOB grew in response to the N substrate additions and were inhibited by both inhibitors, AOA showed little or no response to either the N substrate or inhibitor treatments. In contrast, comammox Nitrospira clade B were inhibited by the high ammonium concentrations released from the urine substrates. These results demonstrate the differential and niche responses of the three ammonia oxidising communities to N substrate additions and nitrification inhibitor treatments. Further research is needed to investigate the specificity of the two inhibitors on the different ammonia oxidising communities.